Utilização de simulações computacionais no ensino de física, na área da termologia - Campos, Bruno De Oliveira (2017)
In this work we would like to introduce the creation of a web server, and along with it we used an off-line site to provide computational simulations to the Physics Teaching in the area of Thermology.The chosen area is due to the contents being taught in the class of the Second year of high school at Public School “Dr. Emílio Silveira,” in the city of Alfenas, State of Minas Gerais. Since we would apply the computer simulations in a computer lab as practical classes, some practical classes were elaborated for the applied computational simulations. The practical lesson plans were elaborated based on David Ausubel's Theory of Significant Learning. The computational simulations used in this work were developed by the Technology in Physics Teaching (PhET) project of the University of Colorado, they are available for free of charge and online.